The English that we have and the English that we need / Kamisah Ariffin, Misyana Susanti Husin and Roselina Musahar - Ariffin, Kamisah; Husin, Misyana Susanti; Musahar, Roselina (2003)
The rapid globalization and development of the 20th and 21 SI centuries have called for the need of the people to be proficient in English. The current resurgence of English as the medium of instruction for Science and Mathematics shows the recognition that proficiency in that language is one of the major determinants in enhancing education and knowledge, and a necessary prerequisite for career enhancement. However, the implementation of the New Education Policy 1971, making Bahasa Malaysia as the medium of instruction in all national schools, has pushed English into a 'low key position' (Asmah 1992), and this move is viewed as one of the factors resulting into the declination of the proficiency in English among Malaysians (Jamali et al 1980). In addition, Gill (1994 : 71) claims that 'we are developing a generation who is only able to speak what some parties call the colloquial variety or simply bad English'. Thus, this paper looks at some evidence on the use of this 'bad' English in several media of writing produced by students and academics, and discusses the need to improve such use of the language. This is because the majority of this generation has been criticized by both public and private sectors with regards to their quality of English. In addition, the government's chief concern is that declining standards of English could hinder Malaysia's progress towards achieving developed nation status' (Fong Chang Onn 1991).